Estimation and Comparative Analysis of Pulmonary Function Parameters across Trimesters of Pregnancy and in Non-pregnant Women including Association of Peak Expiratory Flow Rate and Forced Expiratory Volume: - Yadav, Renu; Yadav, Subodh Kumar (Birat Journal of Health Sciences, 2025)
Introduction : Pregnancy is a physiological condition associated with numerous systemic changes across the trimesters. The respiratory system undergoes significant alterations due to mechanical factors, hormonal influences and activity-related needs of the mother and also driven by the increasing metabolic demands of the developing fetus.Objectives: The objective of this study was to assess the normal values of commonly used pulmonary function parameter (PFT) across different trimesters of pregnancy and to compare it with normal.Methodology: It was a longitudinal study to assess the pulmonary function test for the pregnant women (experiment, E) at different trimester and was compared with age, height and weight matched non-pregnant women (control, C). Convenient, purposive sampling technique was employed to collect the data for pregnant (Experiment=76) and non-pregnant women (Control=76) attending the obstetrics and gynecology department of Nobel Medical College and teaching hospital (NMCTH). Ethical clearance was granted by ethical review committee of NMCTH. SPSS version 24 was used for descriptive analysis of all variables and one-way ANOVA (Post Hoc) to compare the means of pulmonary function test.Results: The mean age (E=32±3.77, C= 32.47±4.30, p=0.471)), height (E=1.58±.02, C= 1.57±.02, p=0.131), weight (E=56.81±1.04, C=56.67±1.06, p=.440) were analyzed which was non-significant. Tidal volume (TV) and respiratory rate (RR) significantly increased (p